Optimasi Formula Sediaan Krim Sunflower (Helianthus annuus L.) Oil - Eva Husein; Agatha Budi Susiana lestari (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Sunflower oil is one of the components of moisturizing cream that keeps the moisture of the skin. To produce a good quality cream, it is necessary to select appropriate emulsifying agent. This study aims to find the optimum composition between Tween 80 and Span 80 as an emulsifying agent in the preparation of sunflower oil cream, to meet physical properties and physical stability in terms of viscosity, spread ability and viscosity shift for 30 days. The ability of the cream to maintain skin moisture was tested using the Transepidermal Water Loss (TEWL) method. This study used a 22 experimental research design with the Simplex Lattice Design. The results showed there are 3 formulas of Tween 80 and Span 80 in proportion (6:4)%, (7;3)% and (8:2)% that fulfill the requirements with 143,3-153,3 dPas in viscosity, spread ability in range 5,0-5,3 cm, and viscosity shift between 4,3-6,8%. Based on TEWL test, the optimum formula obtained has a moisturizing effect with a TEWL value 17,9-38,0%. It conclude, sunflower oil could be formulated into moisturizing cream using combination of Tween 80 and Span 80 in proportion (6:4)%, (7;3)% and (8:2)% to fulfill the requirements for 30 days and could keep the skin moisture.